PENINGKATAN HASIL BELAJAR IPA MENGGUNAKAN METODE INKUIRI DI KELAS IV SEKOLAH DASAR NEGERI 07 SERUKAM - Gedion, Gedion; Rosnita, Rosnita; Sabri, Tahmid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractÂ The problem of this research is "Is using inquiry method in Natural Science Learning can Improve Student Result of Grade IV Primary School of Serukam 07 State Element". The purpose of this study is to describe the improvement of students' learning outcomes in Natural Science learning about style using inquiry method in Class IV SDN 07 Serukam.Â  This research method using descriptive method. The subjects are the fourth grade students of Elementary School Serukan 07 Serukan, the instruments used consist of teacher observation sheets (APKG I and II) and students (final test of IPA). The data analysis for sub-problems I and 2 uses the average formula, the sub-sequence of problem 3 using the percentage formula. The data sources are fourth grade students and teachers (researchers). The research procedure includes planning, action implementation, observation and reflection. (1); The results of the implementation of teacher's ability in science learning plan students have an increase that is on the first cycle is 56 with an average score of 3.11 and categorized "satisfy / good". (2); The results of the implementation of the teacher's ability in implementing science learning students have increased in the first cycle score of 94 with an average score of 3.35 and can be categorized as "satisfactory / good". (3); The result of science learning of students using the method of inquiry in each cycle always has an increase that is on the first cycle of classical average 66.30 with 62.96% classical learning completeness and in cycle II the average value of classical 80.74 with mastery learning classically 88.88%. The conclusion that by using inquiry method in Natural Science learning can improve the result of fourth grade students of Primary School Serukam 07. The improvement of student learning outcomes from cycle I to cycle II was 14.44 points with a percentage of 25.92%.Keywords: Student Learning Outcomes, Science Lesson, Inquiry Method